Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Produk Di Tokopedia - Rahma Juliyani; Anisti; Tuty Mutiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The rapid development of digitalization has led to changes in how consumers shop, especially on e-commerce platforms. Tokopedia, as one of the largest online marketplaces in Indonesia, implements various marketing methods, including the use of brand ambassadors to attract attention and influence buyers' decisions. The purpose of this study is to investigate the effect of brand ambassadors, in this case the South Korean boy band BTS, on consumers' shopping decisions on Tokopedia. This study employs a quantitative approach and uses a survey method. The instrument used is a questionnaire with a Likert scale, analyzed through validity, reliability, descriptive analysis, and simple linear regression. The results indicate that brand ambassadors have a positive and significant impact on purchasing decisions on Tokopedia. These findings support the AIDA theory, which indicates that brand ambassadors can attract attention, increase interest, trigger desire, and encourage purchasing actions. Therefore, selecting brand ambassadors that align with demographic characteristics, such as BTS for a younger audience, is considered effective for strengthening marketing communication strategies in the e-commerce sector.